Effect of plasma exchange on blood viscosity and cerebral blood flow. Issue 6331 (12th June 1982) - Brown, M M; Marshall, J
Abstract : The effects of plasma exchange using a low viscosity plasma substitute on blood viscosity and cerebral blood flow were investigated in eight subjects with normal cerebral vasculature. Plasma exchange resulted in significant reductions in plasma viscosity, whole blood viscosity, globulin and fibrinogen concentration without affecting packed cell volume. The reduction in whole blood viscosity was more pronounced at low shear rates suggesting an additional effect on red cell aggregation. Despite the fall in viscosity there was no significant change in cerebral blood flow. The results support the metabolic theory of autoregulation. Although changes in blood viscosity appear not to alter the level of cerebral blood flow under these circumstances, plasma exchange could still be of benefit in the management of acute cerebrovascular disease.